Hydatid cyst of the left gluteal region - Chavarría, Oscar (Cirugía del Uruguay, 1972)
A five-year-old girl, presenting a hydatid cyst in a muscle, in a rather unusual topography, is the subject of this paper which refers to its ethiopathogenesis, symptomatology and treatment.